Goodwin Model with Clustering Workers' Skills in Indonesian Economic Cycle - Mahmud, Sri Lestari; Resmawan, Resmawan; Ismail, Sumarno; Nurwan, Nurwan; Taki, Febriani (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
The economic model which deals with the economic cycle is Goodwin's Model. It presents the relationship between the employment rate and wage shares. In this study, the modification model was made, taking into three types of workers, namely high, medium, and low-skilled workers. Studies of the model are conducted by determining the equilibrium point and its stability analysis. Furthermore, a numerical simulation is given to see which model satisfies the ideal of Goodwin‘s model cycle prediction by using Indonesian data from 2000 to 2020. In the end, an investigation into the effects of reducing the wage gap between the three types of workers was conducted. The results showed two equilibrium points, namely The Equilibrium Point without Employment Rate and The Wages Share (T1) and the Existence Equilibrium Point of Employment Rate and Wages Share (T2). T1 achieves a stable node condition when ScQd+pi+et while T2 reaches a stable center condition when ScQd+pi+et. The simulation showed Goodwin's model of high- and low-skilled workers produced the ideal of Goodwin model cycle predictions, whereas Goodwin's model of medium-skilled workers and the entire economy (capitalist) didn’t produce the ideal of Goodwin model cycle predictions. Eventually, the effects of reducing the wage gap make the economy unstable.